Highlight selection of radiochemistry and radiopharmacy developments by editorial board (January-June 2020) - Mohammed Al-Qahtani; Martin Behe; Guy Bormans; Giuseppe Carlucci; Jean Dasilva; Clemens Decristoforo; Philip H. Elsinga; Klaus Kopka; Xiang-Guo Li; Robert Mach; Oskar Middel; Jan Passchier; et al. (SpringerOpen, 2021)
Abstract Background The Editorial Board of EJNMMI Radiopharmacy and Chemistry releases a biyearly highlight commentary to describe trends in the field. Results This commentary of highlights has resulted in 19 different topics selected by each member of the Editorial Board addressing a variety of aspects ranging from novel radiochemistry to first in man application of novel radiopharmaceuticals. Conclusion Trends in radiochemistry and radiopharmacy are highlighted demonstrating the progress in the research field being the scope of EJNMMI Radiopharmacy and Chemistry.